2017
DOI: 10.1042/ebc20170023
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy impairment in Parkinson’s disease

Abstract: Parkinson's disease (PD) is a debilitating movement disorder typically associated with the accumulation of intracytoplasmic aggregate prone protein deposits. Over recent years, increasing evidence has led to the suggestion that the mutations underlying certain forms of PD impair autophagy. Autophagy is a degradative pathway that delivers cytoplasmic content to lysosomes for degradation and represents a major route for degradation of aggregated cellular proteins and dysfunctional organelles. Autophagy up-regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
90
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(96 citation statements)
references
References 89 publications
1
90
0
Order By: Relevance
“…Defects in lysosomes are common denominators of neuronal diseases and found in, for example, Alzheimer's (Zare-Shahabadi et al, 2015), Parkinson's (Karabiyik et al, 2017) and Huntington's disease (Zhao et al, 2016). Lysosome-associated neurodegeneration is induced by a combination of mechanisms, most importantly, the accumulation of undegraded material (Jiang et al, 2014) and dysregulated signaling (Peng et al, 2012a).…”
Section: Neurological Defectsmentioning
confidence: 99%
“…Defects in lysosomes are common denominators of neuronal diseases and found in, for example, Alzheimer's (Zare-Shahabadi et al, 2015), Parkinson's (Karabiyik et al, 2017) and Huntington's disease (Zhao et al, 2016). Lysosome-associated neurodegeneration is induced by a combination of mechanisms, most importantly, the accumulation of undegraded material (Jiang et al, 2014) and dysregulated signaling (Peng et al, 2012a).…”
Section: Neurological Defectsmentioning
confidence: 99%
“…In recent years, several pieces of evidence suggest that autophagy plays an important role in neurogenic disorders, such as HD, PD, Alzheimer's, and amyotrophic lateral sclerosis (Karabiyik, Lee, & Rubinsztein, 2017;Ouyang et al, 2018;Shi et al, 2012). However, other studies have shown that excessive autophagy could be related to neuronal death in cerebral ischemia (Fornai et al, 2008;Kabuta, Suzuki, & Wada, 2006;Shi et al, 2012).…”
Section: Ormond Et Al In a Study Used Stem Cells Alone Or In Combinamentioning
confidence: 99%
“…Andrew Tee and Charlotte Johnston [11] provide an excellent primer on cancer autophagy and how mTOR-dependent signalling and regulation of autophagy in neoplastic disease offers potential vulnerabilities that provide tractable therapeutic targets that may work in certain disease contexts. The role of autophagy in Parkinson's disease is supported by evidence that Parkinson's disease-associated genes lead to autophagy impairment and so David Rubinzstein and colleagues [12] explain how this leads to disease pathology, but also more importantly, how our evolving understanding of brain autophagy could pave the way for exiting new therapies for the treatment of Parkinson's and possibly other neurodegenerative diseases. Cancer and neurodegenerative diseases are poignantly debilitating diseases, with the former associated with high disease recurrence risk and mortality, and the latter with progressive loss of cognitive abilities and control.…”
mentioning
confidence: 94%